Bibliometric Analysis of Magnetite Nanoparticle Production Research During 2017-2021 Using Vosviewer - Agung Slamet Nugraha (Universitas Pendidikan Indonesia (UPI), 2022)
Fe3O4 nanoparticles are magnetic materials that can use in various fields. Fe3O4 particles have several properties such as being super magnetic, having a high saturation field, being chemically stable, biocompatibility, and low production costs. The purpose of this study was to conduct a bibliometric analysis of the research on the production of Fe3O4 nanoparticles by using mapping analysis with VOSviewer software. The data used in the study were obtained and collected using the Publish or Perish software. The data obtained were obtained based on the keywords